Gastric outlet obstruction caused by an ectopic pancreas in a neonate: A case report - Shunsuke Fujii; Hideaki Tanaka; Kentaro Ono; Yutaro Onizawa; Yayoi Miyazono; Naoya Sakamoto; Chikashi Gotoh; Yasuhisa Urita; Toko Shinkai; Hajime Takayasu; Ryo Sumazaki; Kouji Masumoto (Elsevier, 2015)
We herein report a neonate who presented with non-bilious vomiting at one day of age caused by a prepyloric ectopic pancreas. Ultrasonography clearly detected the presence of a submucosal mass preoperatively, which was treated with local gastric resection. Only 9 neonates with a symptomatic pyloric or prepyloric ectopic pancreas have been previously reported in the literature. Therefore, we reviewed and discussed the clinical features of neonates with this type of ectopic pancreas.